Female predominance and over forty years of age, in patients with gallstones diagnosed and treated with ERCP in Venezuela (Salud, Arte y Cuidado, 2024)
Introduction. The scarce information in Venezuela, on the relationship between gallstones, patient sex and age groups, supported by the diagnosis and treatment of Endoscopic Retrograde Cholangiopancreatography (ERCP), motivated the present manuscript. Methodology. A cross-sectional descriptive study was carried out on 249 patients who voluntarily underwent ERCP due to a history of liver, biliary, pancreatic, lithiasis problems or their combinations. Results. 92 patients presented problems with gallstones and of these the female sex was predominant with 75 female patients, which corresponds to 82% of those examined, also the age group of 51 to 60 years was the most frequent with 21% of the total of patients studied. Conclusion. The present results, in Venezuela, correspond to the female majority reported in the rest of Latin America, but on this occasion, it is the highest female percentage in the entire region. This female predominance is due to a series of physiological characteristics, which makes them more prone to gallstones, a situation that generally increases with age, so an annual abdominal echo, applied to these risk groups, would be a way early and timely diagnosis of the onset of gallstones, so it would be easier to perform cholecystectomy electively, avoiding complications such as gallstones.